2020
DOI: 10.5194/isprs-archives-xliii-b3-2020-1333-2020
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Accuracy Assessment of Google Earth Data Over Typical Regions of Asia

Abstract: Abstract. Google Earth provide the most accurate and available global high resolution imagery, covering nearly the entire land surface of the earth. However, the precision of Google Earth’s data has not been fully validated.The traditional ground measurement method is difficult to verify the horizontal precision of remote sensing over a large area. This paper focuses on typical regions of Asia, aiming to verify the precision of GE’s data based on purchased WorldView (WV) data by utilization of statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The detection of the grid cells falling on water ponds or on emerged land was determined with a visual inspection method in QGIS using Google Earth satellite as base image. Google Earth is the most accurate highresolution virtual globe currently available and covers almost the entire land surface of the Earth (Yu and Gong 2012;Guo et al 2020). It integrates aerial photographs with medium to high spatial resolution satellite images mainly collected by WorldView-1/2/3, GeoEye-1, Airbus' Pleiades, QuickBird, Landsat and SPOT5.…”
Section: Landsat 8 Oli Spatial Resolution Is Not Adequate To Study So...mentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of the grid cells falling on water ponds or on emerged land was determined with a visual inspection method in QGIS using Google Earth satellite as base image. Google Earth is the most accurate highresolution virtual globe currently available and covers almost the entire land surface of the Earth (Yu and Gong 2012;Guo et al 2020). It integrates aerial photographs with medium to high spatial resolution satellite images mainly collected by WorldView-1/2/3, GeoEye-1, Airbus' Pleiades, QuickBird, Landsat and SPOT5.…”
Section: Landsat 8 Oli Spatial Resolution Is Not Adequate To Study So...mentioning
confidence: 99%
“…The horizontal accuracy of Google Earth varies for different locations of the world and is strongly affected by topography, being lower on mountainous terrain and higher on plains. Several studies have shown that on plains and lowlands the absolute positioning accuracy generally varies between 0.1 and 5.0 m (Benker et al 2011;Paredes-Hernandez et al 2013;Goudarzi and Landry Jr 2017;Guo et al 2020). The disadvantage is that Google Earth is a collage of images collected very recently but in different periods, and some landuse changes may have occurred since 2017, when the L8 image used in this study was acquired.…”
Section: Landsat 8 Oli Spatial Resolution Is Not Adequate To Study So...mentioning
confidence: 99%
“…The results show that the accuracy evaluation may be affected by the terrain features and unimportant feature points in the study area. (6) A DEM can also provide elevation information for a target; therefore, evaluating its accuracy is essential. Li et al selected five samples of typical terrain in China to evaluate the vertical accuracies of the AW3D30 and SRTM DEMs.…”
Section: Introductionmentioning
confidence: 99%
“…Google Earth Studio is one of the most popular Google Earth and virtual globe applications that offer most of the planet free access to high-resolution imagery. According to scientific indexes, Google Earth (GE) has been downloaded more than 1 billion times on desktop and mobile clients since the introduction of the Google Earth software in 2005 (Guo et al, 2020).…”
Section: Introduction In Google Earth Studiomentioning
confidence: 99%